Behaviour of steel-jacket retrofitted RC columns with preload effects. (December 2016) - He, An; Cai, Jian; Chen, Qing-Jun; Liu, Xinpei; Xu, Jin
Abstract: Steel jacketing is an efficient way to retrofit reinforced concrete columns. Previous studies focused on the performance improvement without considering the preloads on the original columns. The preloads might inevitably affect the structural performance of the retrofitted columns. Comprehensive experimental and numerical studies on the behaviour of steel-jacket retrofitted RC columns with preload effects are presented in this paper. Twenty-nine steel jacketing columns with different steel tube thicknesses, axial preloading levels and load eccentricities are tested under concentrically or eccentrically compressive loading. The experimental results are discussed and illustrate that the effects of preloading levels on the axial compression strength of the retrofitted columns are negligible while increasing the preloads could decrease the eccentric compressive strength. A fibre element model is developed to predict the behaviour of the retrofitted columns. The material non-linear behaviour of all the components considering the steel tube and stirrup confining effects on the concrete as well as the preloading action are taken into account in the model. The model is validated by comparing its results with the experimental results. Extensive parametric studies are undertaken by using the proposed numerical model to elucidate the effects of axial and moment preloading and the effects of preloads with various other parameters on the performance of the retrofitted columns. Highlights: Preload effects of steel-jacket retrofitted RC columns are studied. A fibre element model is developed to predict the behaviour of the retrofitted columns. Effects of various axial force and moment preloading on the strengths of the retrofitted columns are discussed.